No sé qué day: Code-switching and code-mixing in a plurilingual family living in Catalonia - Jill Simon Auerbach (Bellaterra Journal of Teaching & Learning Language & Literature, 2011)
This study analyzes the unique plurilingual (Catalan, Spanish and English) speech of a family living in Catalonia in order to understand the  variety of forms in which linguistic multicompetence is made manifest in their dialogues.. Factors that were found to influence code-switching and code-mixing in dialogues among family members include: the context of the conversation, the expression of distinct discursive voices, the affective consequences of employing the dominant or non-dominant language of the interlocutor, the ingrained nature of discourse markers, resistance to changing the names of academic concepts or courses, and the desire to creatively combine elements of distinct language systems to suit the expressive needs of the speaker. An argument is made in favor of a distinction being made between linguistic variety and communicative code as well as for a user-based, pragmatic view of language knowledge.